A recall of Parliamentarians: a prospective accountability - Bhanu, Vinod (2007)
It is time Indian voters got the right to recall non-performing elected representatives and a chance to suggest to the parties their choice of candidates. An extra-parliamentary body must also be set up to scrutinise the conduct of Members of Parliament inside and outside the House. - Reproduced.
Keywords: Legislators - India; India. Parliament; Parliament